Effects of caffeine consumption on sports performance (scoping review) - Rajamohan, Manjjhari (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Caffeine is one of the most common ergogenic compounds used in sports, and its efficacy is supported by a strong body of evidence that demonstrated improvement in both anaerobic and aerobic performance. The prevalence of caffeine use in athletes has been examined since the withdrawal of caffeine from the banned list of the World Anti-Doping Agency in 2004. The overall daily caffeine intake for most athletes, including pre-and intra-training doses, should not exceed 3 mg/kg body weight, as this will greatly increase the minimum pre-competition caffeine dose to elicit any ergogenic effect. Therefore, this review aims to determine the effect of caffeine consumption on sports performance, types and dosage of caffeine consumed and the timing of its consumption among athletes and physically active individuals. Related studies were searched electronically using the following databases: Scopus, PubMed, EbscoHost and ScienceDirect. The analysis was done in compliance with the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). From the 14 included studies, all the studies were conducted on humans. The scope of study from those retrieved articles was primarily on the effects of caffeine consumption on sports performance. The total number of participants for all the 14 articles are 217 male participants. The study design in these reviewed articles include randomised placebo-controlled trial and double-blind cross-over design. In terms of exercise protocol to measure performance outcome in the articles reviewed, twelve studies reported on time trial performance while another two studies reported exercise time to exhaustion. Eight studies reported on caffeine intervention protocol before the exercise session, five studies reported caffeine intervention protocol during Caffeine is one of the most common ergogenic compounds used in sports, and its efficacy is supported by a strong body of evidence that demonstrated improvement in both anaerobic and aerobic performance. The prevalence of caffeine use in athletes has been examined since the withdrawal of caffeine from the banned list of the World Anti-Doping Agency in 2004. The overall daily caffeine intake for most athletes, including pre-and intra-training doses, should not exceed 3 mg/kg body weight, as this will greatly increase the minimum pre-competition caffeine dose to elicit any ergogenic effect. Therefore, this review aims to determine the effect of caffeine consumption on sports performance, types and dosage of caffeine consumed and the timing of its consumption among athletes and physically active individuals. Related studies were searched electronically using the following databases: Scopus, PubMed, EbscoHost and ScienceDirect. The analysis was done in compliance with the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). From the 14 included studies, all the studies were conducted on humans. The scope of study from those retrieved articles was primarily on the effects of caffeine consumption on sports performance. The total number of participants for all the 14 articles are 217 male participants. The study design in these reviewed articles include randomised placebo-controlled trial and double-blind cross-over design. In terms of exercise protocol to measure performance outcome in the articles reviewed, twelve studies reported on time trial performance while another two studies reported exercise time to exhaustion. Eight studies reported on caffeine intervention protocol before the exercise session, five studies reported caffeine intervention protocol during